-7(x+2)=x-8+2(3x+2)

Simple and best practice solution for -7(x+2)=x-8+2(3x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+2)=x-8+2(3x+2) equation:



-7(x+2)=x-8+2(3x+2)
We move all terms to the left:
-7(x+2)-(x-8+2(3x+2))=0
We multiply parentheses
-7x-(x-8+2(3x+2))-14=0
We calculate terms in parentheses: -(x-8+2(3x+2)), so:
x-8+2(3x+2)
determiningTheFunctionDomain x+2(3x+2)-8
We multiply parentheses
x+6x+4-8
We add all the numbers together, and all the variables
7x-4
Back to the equation:
-(7x-4)
We get rid of parentheses
-7x-7x+4-14=0
We add all the numbers together, and all the variables
-14x-10=0
We move all terms containing x to the left, all other terms to the right
-14x=10
x=10/-14
x=-5/7

You can always share this solution

See similar equations:

| 2g=-5+3g | | 15d+20=110 | | -9u=-8u+7 | | x-25=18;= | | 15j=2+14 | | 4p=2p-8 | | 21=z?53 | | 50=z+-4 | | E^-x=245 | | d+87=-8 | | 1.5t^2+4.9t+2=0 | | 4(-8x-12)=-26-32x | | -3x+7-6(x-1)=-(2x-4)-6x+6 | | b^2+5=17 | | z?-41=54 | | 4u-36=6(u-5) | | d?698=-271 | | -216=-6(1-5r) | | x-4-15=10 | | -7y+2(y-2)=31 | | 7(n=4)21 | | 3(-4-6b)=114 | | 181=84-w | | -140=5(4a-4) | | k-875=-750 | | y=4×5+12 | | k?875=-750 | | -8q=-88 | | -m+8(5-8m)=300 | | -3t=-78 | | 6x-4(3-2x)=4(x-4)-36 | | 41=6g+5 |

Equations solver categories